Antithrombin III Kumamoto: Identification of a Point Mutation and Genotype Analysis of the Family - Ueyama, Hidetsugu; Murakami, Tatsufumi; Nishiguchi, Seiji; Maeda, Shuichiro; Hashimoto, Yoichiro; Okajima, Kenji; Shimada, Kazunori; Araki, Shukuro (Thrombosis and Haemostasis, 1990)
We previously reported a variant antithrombin III (AT III Kumamoto) associated with a 31-year-old female who suffered from recurrent thrombotic episodes (1). To define the molecular basis for the variant AT III, we used a combination of genomic amplification followed by cloning, sequencing, and hybridization with allele-specific oligonucleotide probes. We obtained evidence for a cytosine to thymine transition in exon 2 (codon 47) of the AT III gene in the proband. This mutation converts arginine 47 to cysteine. Oligonucleotide hybridization procedures were used for confirmation of the mutation and for genotype analysis of the family members